Sosialisasi Tanggap Bencana Covid-19 Di Desa Batu Balian Kecamatan Simpang Empat Kabupaten Banjar Provinsi Kalimantan Selatan - Apriansyah; Lalita Hanief; Andhika Wiguna Briantama; Dewi Utari; Dimas Fernandayarin; Elisa Yulianti; Hilda Elia Ningsih; Muhammad Fariz; Sukma Endah Darmayanti (Journal of Empowerment and Community Service (JECSR), 2021)
The community in Batu Balian Village has various characteristics. There are several RTs whose people do not have more awareness to comply with existing health protocols, people also tend not to believe in the existence of the Covid-19 Virus. So we need a particular action/method used to solve the problem. Therefore, it is necessary to carry out Socialization activities to Build a Covid-19 Disaster Response Village in Batu Balian Village. This research uses the socialization method. The socialization was carried out to students of the Government Science Study Program, FISIP University of Lambung Mangkurat. This socialization was carried out to educate the Batu Balian village community about the dangers of, preventing, and overcoming the Covid-19 disaster, amid the widespread spread of Covid-19 and how to carry out standard operating procedures in isolating when exposed to Covid-19. As well as explaining the various impacts that occur amid the Covid-19 pandemic, both economic, social, and ecological.